Antibacterial And Cell Interaction Of Ti02-Based Nanoparticles And Nanotubes - Ahmad Barudin, Nur Hidayati (2014)
Currently, some of the major problems affecting the world are air pollution as well as microbial contamination. Every time we breathe, we are risking our lives by inhaling dangerous chemicals and biological contaminants that have found their way into the air. In this work, the use of Ti02 photocatalyst materials to overcome indoor air pollutants is investigated. The Ti02 nanosolution was prepared by using sol-gel method followed by the peptization process at 85 °C for 8 hours.